Aberrant lncRNA and mRNA expression in patients with anti-N-methyl-d-aspartate receptor encephalitis - Ma, Xiaoyu; Guo, Wenbo; Teng, Zixuan; Yin, Qingqing; Wang, Chunjuan; Wang, Pin; Guo, Shougang (Frontiers in Neurology, 2025)
BackgroundAnti-N-methyl-d-aspartate receptor (anti-NMDAR) encephalitis is a nervous autoimmune disorder discovered in the recent more than 15 years. To understand potential involvement of epigenetic mechanisms in pathogenesis of anti-NMDAR encephalitis, we initiated a study to compare the expression profiles of long non-coding RNAs (lncRNAs) and messenger RNA (mRNAs) in patients of anti-NMDAR encephalitis and healthy controls.MethodsEleven patients who were diagnosed with anti-NMDAR encephalitis were enrolled in our observational studies. Total RNA was extracted from patients’ plasma and the expression levels of lncRNAs and mRNAs were determined. Differential expression analysis via RNA sequencing, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, as well as a co-expression network of lncRNA-mRNA were performed in 5 patients and 5 healthy controls to evaluate potential the changes in expression patterns. The expression levels of certain lncRNAs and mRNAs were further validated in 11patients and 11 healthy controls using quantitative real-time polymerase chain reaction (qRT-PCR).ResultsIt was found that a total of 83 lncRNAs and 2,345 mRNAs were differentially expressed in five patients with anti-NMDAR encephalitis compared with five healthy controls. Of those lncRNAs, 63 were upregulated and 20 downregulated, while 1,509 mRNAs were upregulated and 836 downregulated. GO and KEGG pathway analyses showed that a wide range of biological functions were perturbed during acute anti-NMDAR encephalitis. Differentially expressed genes were found to be involved in autoimmune, B cell signaling, neuroinflammation, or synaptic plasticity. qRT-PCR was conducted in 11 patients and 11healthy controls to further confirm the levels of six lncRNAs and four mRNAs, and the results were found to be consistent with those by RNA sequencing. The co-expression networks of lncRNA-mRNA were performed in some meaningful KEGG analyses, including chemokine signaling pathway, Long-term potentiation, B cell receptor signaling pathway and MAPK signaling pathway.ConclusionTaken together, these findings suggest the involvement of a number of molecular pathways in anti-NMDAR encephalitis, some of which could serve as potential biomarkers to assist in diagnosis, treatment and prognosis.